PERAN UNITED NATIONS COMMITTEE ON THE PEACEFUL USES OF OUTER SPACE DALAM PEMANFAATAN TEKNOLOGI SATELIT PENGINDERAAN JAUH PADA MASA PANDEMI COVID-19 DI INDONESIA DITINJAU DARI HUKUM RUANG ANGKASA - Indah Tri Wisesha; Zulfikar Jayakusuma; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
International organization take a role in the problem of space explorationand exploitation, for this reason an international organization that is engaged inspace law is needed, namely the United Nations Committee. on the Peaceful Usesof Outer Space (UNCOPUOS technology. In the case of COVID-19 remotesensing technology plays a role in mitigating the spread of COVID-19, butproblems arise when not all can take advantage of satellite technology, especiallydeveloping countries like Indonesia.The type of research used in this paper uses normative legal researchmethods. In this research, the authors conducted research on legal principles inspace treaties and theories about the role of international organizations whichwill examine the extent of UNCOPUOS role and how to use remote sensingsatellite technology during the COVID-19 pandemic.The results of the problem research it was found that: First, UNCOPUOShad not carried out its role in making the regulations listed in UN MU ResolutionNo. 1472 (XIV) dated December 12, 1959, especially in the regulations for the useof remote sensing technology which were not yet adequate and could even be saidto be still a vacuum in relation to remote sensing activities via satellite. Second,the use of remote sensing satellite technology during the COVID-19 pandemicwhere LAPAN only provided information and was not directly involved in its use.UNCOPUOS' efforts as an international organization are only limited todiscussions at the UNOOSA scientific sub-committee, therefore it is stillconsidered not to guarantee that developing countries like Indonesia will get theirrights.Keywords: Space Law - UNCOPUOS - Remote Sensing Satellite